Re-evaluation of the fossil penguin Palaeeudyptes gunnari from the Eocene Leticia Formation, Argentina: additional material, systematics and palaeobiology - Acosta Hospitaleche, Carolina Ileana Alicia; Olivero, Eduardo Bernardo (Alcheringa: An Australasian Journal of Palaeontology)
Re-evaluation of the fossil penguin Palaeeudyptes gunnari from the Eocene Leticia Formation, Argentina: additional material, systematics and palaeobiology. Alcheringa 40, xx–xx. ISSN 0311-5518 Eocene penguins are known mostly from Antarctic specimens. A previously documented partial skeleton consisting of a pelvis, femur, tibiotarsus and fibula, from the middle Eocene Leticia Formation, Tierra del Fuego Province, Argentina, has been prepared and re-described. Re-analysis favours assignment to Palaeeudyptes gunnari, a species widely recorded in the Eocene of Antarctica. A new isolated coracoid belonging to an indeterminate species reveals new information about diving kinematics and swimming abilities. Palaeobiological attributes and morphology of the fossils indicate that both specimens belonged to large penguins with poor diving capability and wing propulsion systems similar to those of extant taxa. These penguin remains are the only vertebrate fossils thus far recorded from the Leticia Formation, and provide important insights into the relationships of South American and Antarctic penguins during the Paleogene. The presence of Palaeeudyptes in Argentina supports an Eocene connection between the South American and Antarctic penguin faunas. Carolina Acosta Hospitaleche [acostacaro@fcnym.unlp.edu.ar], CONICET. División Paleontología Vertebrados, Museo de La Plata Paseo del Bosque s/n, 1900 La Plata, Facultad de Ciencias Naturales y Museo, UNLP, Argentina; Eduardo Olivero [emolivero@gmail.com], CONICET. Centro Austral de Investigaciones Científicas (CADIC-CONICET), B. Houssay 200, 9410 Ushuaia, Tierra del Fuego, Argentina. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina